2022
DOI: 10.21203/rs.3.rs-1983481/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metadichol® induced expression of neuronal transcription factors with Human fibroblast Dermal cells

Abstract: Background. Producing neurons from fibroblast cells has the potential to treat neurodegenerative diseases, characterized by neuron loss. Neurodegenerative diseases are a growing problem in the current aging, developed world populations. Metadichol® is a nontoxic nanoemulsion of long-chain lipid alcohols, currently available as an oral supplement. Methods and Findings. In this study, Metadichol® was used to treat human fibroblasts in vitro; we subsequently evaluated changes in the expression of neuronal transc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Forester et al [30][31] suggested that the liganded vitamin D receptor (VDR) upregulates Klotho via vitamin D response elements (VDRE). Metadichol is a VDR inverse/protein agonist [32][33]. Among the consequences of the enhanced expression of Klotho is an increase in telomerase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Forester et al [30][31] suggested that the liganded vitamin D receptor (VDR) upregulates Klotho via vitamin D response elements (VDRE). Metadichol is a VDR inverse/protein agonist [32][33]. Among the consequences of the enhanced expression of Klotho is an increase in telomerase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Metadichol targets these genes as well (64 Metadichol has all the characteristics needed to reverse aging-related diseases. Based on our previous work (64)(65)(66)(67). Metadichol ® represents the rst of a class of safe therapeutics that target MRGs affecting multiple genes, pathways, and diseases…”
Section: Resultsmentioning
confidence: 99%
“…Metadichol ® represents the rst of a safe class of therapeutics that target multiple genes, pathways [59][60][61][62] and multiple diseases, which points to importanceof a relevance of the network-based approach. 63…”
Section: Therapeutic Strategymentioning
confidence: 99%